2019
DOI: 10.1101/859892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interplay betweenTERTpromoter mutations and methylation culminates in chromatin accessibility andTERTexpression

Abstract: AbstractThe telomerase reverse transcriptase (TERT) gene is responsible for telomere maintenance in germline and stem cells, and is re-expressed in 90% of human cancers. Contrary to common concepts, CpG methylation in the TERT promoter (TERTp), was correlated with TERT mRNA expression. Furthermore, two hotspot mutations in TERT Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
5
3
0
Order By: Relevance
“…The enrichment of TERT promoter mutations in certain tissues has inspired several explanations, and our findings in both the CCLE and TCGA suggest a specific epigenetic signature that may underlie this unique pathway of telomere maintenance. We found that in TERT promoter mutants, CpG islands were preferentially hypomethylated in PRC2-repressed regions located near telomeres, which may relate to previous reports of a long-range telomere position effect (W. Kim et al, 2016;Yuan et al, 2019) and of TERT expression necessitating specific chromatin states in promoter-wildtype and mutant samples (Salgado et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The enrichment of TERT promoter mutations in certain tissues has inspired several explanations, and our findings in both the CCLE and TCGA suggest a specific epigenetic signature that may underlie this unique pathway of telomere maintenance. We found that in TERT promoter mutants, CpG islands were preferentially hypomethylated in PRC2-repressed regions located near telomeres, which may relate to previous reports of a long-range telomere position effect (W. Kim et al, 2016;Yuan et al, 2019) and of TERT expression necessitating specific chromatin states in promoter-wildtype and mutant samples (Salgado et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Absolute methylation of the remaining gene body was positively correlated with TERT expression in both promoter status contexts ( Supplementary Fig. 8d), which parallels previous reports of a positive correlation between TERT expression and methylation (Barthel et al, 2017;Salgado et al, 2019). Exon 1 methylation was elevated in nearly all cell lines with monoallelic TERT expression in both the mutant promoter context (P = 6.3×10 -3 , two-sided Mann-Whitney U test, n = 81) and the wildtype one (P = 1.6×10 -4 , two-sided Mann-Whitney U test, n = 98) compared to biallelic TERT expressors (Stern et al, 2017).…”
Section: Distinct Tertp Methylation Patterns At the Tert Locussupporting
confidence: 89%
See 1 more Smart Citation
“…The histone mark H3K27me3 maintains heterochromatin and recruitment of the polycomb repressor complex (PRC) for silenced genes (43). Alternatively, the H3K4me3 mark maintains actively transcribed genes in the open confirmation to enable access for transcriptional activators to bind (44). Telomerase negative primary cells exhibit high levels of the silencing H3K27me3 mark at the TERT promoter, compared to telomerase positive cancer cell lines (45), which exhibit the activating H3K4me3 mark (46).…”
Section: Tert Histone Mark Modificationsmentioning
confidence: 99%
“…For example, some allelic variants of the melanocortin 1 receptor (MC1R) can act as genetic modifiers by increasing the penetrance of cyclin-dependent kinase inhibitor 2A (CDKN2A) mutations, doubling the risk of melanoma compared to those only harboring the CDKN2A mutation [9]. However, the hypothesis that heritable germinal epimutations may play a role in the formation of some familial clusters of melanoma, as shown for other neoplasms [10,11] is not supported by conclusive evidence [12].…”
Section: Introductionmentioning
confidence: 99%